The complexities of human procedural nursing research ethical approval processes in Indonesia - Abigail, Wendy; Yulia, Yulia; Christina, Juliana; Pradanie, Retnayu (Universitas Airlangga, 2023)
Introduction: Research requires high quality ethical practices. However, research approvals vary between developed and developing countries resulting in additional challenges for researchers wishing to participate in collaborative research projects. The aim of this paper is to describe and discuss three nursing research ethics application processes in different locations in Indonesia that had an Australian university overseeing them. Methods: Three nurse researchers provide a reflective account of the ethics application processes of their qualitative research projects conducted between 2014 and 2021. A collective case-study methodology using descriptive analysis was applied where the information was collated and compared for similarities, differences and challenges. Results: Ethics and site approvals varied at each Indonesian site. The ethical and approval application processes were time-consuming at all levels. which delayed the start of all the projects, which varied from between one to six months. As a result, all three projects experienced delayed completion. Conclusions: Ethical approval is required for medical research prior to any data collection. Approval processes need to be consistent so that delays in the application processes are avoided. Any delays in approval to conduct research has implications for research projects. It is essential that timeframe factors need to be considered when applying for grant funding, gatekeepers are identified early, and payments are identified and planned for. It is recommended that, to improve consistency with ethical application processes, streamlining of applications and approvals in Indonesia needs to be reviewed, particularly since the introduction of the WHO March 2022 Standard Operating Procedures.